P 78 Involvement of the subthalamic nucleus in the maintenance of cognitive flexibility – Evidence from local field potential recordings. Issue 10 (October 2017) - Paracka, L.; Heldmann, M.; Abdallat, M.; Dressler, D.; Münte, T.; Kopp, B.; Wegner, F.; Krauss, J.K.
Abstract : Functional imaging techniques have revealed that several cortical brain regions like the prefrontal cortex, the anterior cingulate cortex, and the posterior parietal cortex are involved in the maintenance of cognitive flexibility. However, the role of basal ganglia in the ability to switch between several concepts remains largely unknown. To address this issue further we recorded local field potentials via DBS electrodes from the nucleus subthalamicus (STN) while participants performed a task that required executive processes like planning and set shifting. Seven patients with Parkinson disease were included in the study. The patients performed a computerized version of the Wisconsin Card Sorting Test. The participants were required to match the cards according to three possible matching rules (color, shape and number). After the sorting choice was made, a feedback "switch" or "repeat" indicated that the rule had to be changed or repeated respectively. "Integration cue" as a measure of shifting rule with three levels of complexity was compared to "repeat cue" as a measure of keeping the same rule as before. The results show that the amplitudes of the integration cue are larger than those of the repeat cue. Integration condition induced oscillatory changes with the highest power in the theta band in comparison to the repeat condition. Moreover, there is a significant late higher activation of beta band for the integration trials. In conclusion, there are broadband oscillatory changes in the STN during executive processes. STN appears to be involved in shifting cognitive sets and modulating responses.